Case report: A simple and reliable approach for progressive internal distraction of the sternum for Jeune syndrome (asphyxiating thoracic dystrophy): preliminary experience and literature review of surgical techniques - Inserra, Alessandro; Zarfati, Angelo; Pardi, Valerio; Bertocchini, Arianna; Accinni, Antonella; Aloi, Ivan Pietro; Martucci, Cristina; Frediani, Simone (Frontiers in Pediatrics, 2023)
BACKGROUND: Described for the first time in 1954, Jeune syndrome (JS), often called asphyxiating thoracic dystrophy, is a congenital musculoskeletal disease characterised by short ribs, a narrow thorax, and small limbs. This study aimed to analyse and present our preliminary experience with a device for Progressive Internal Distraction of the Sternum (PIDS) in patients with symptomatic JS.Another aim was to review the contemporary English literature on existing surgical techniques for treating children with congenital JS.MATERIAL AND METHODS: A retrospective analysis of paediatric patients (<18 years old) treated for symptomatic JS at our tertiary centre between 2017 and 2023 was performed.RESULTS: We present two patients with JS who underwent surgery using an internal sternal distractor, the Zurich II Micro Zurich Modular Distractor, placed at the corpus of the sternum among the divided halves. CONCLUSIONS: Our experience shows promising results regarding the safety and effectiveness of this less-invasive device for Progressive Internal Distraction of the Sternum (PIDS) in patients with symptomatic JS. Further studies on long-term outcomes are needed to validate these findings.